Investigating the Digital Citizenship Levels of ELT Students within the Scope of Remote Learning - Müfit Şenel (Journal of English Language Teaching and Linguistics, 2022)
It is obvious that using the Internet and technological tools became a ‘must’ throughout the Covid-19 pandemic period. All students and teachers started to use all those tools intensively both in their lessons and at their homes, and this process led to the digitalization of the classrooms and courses. Therefore, information and communication technologies (ICTs) and remote learning spread to all aspects of our lives and led to the emergence of a new concept, namely ‘Digital Citizenship’, making it significant to comprehend where students’ digital competence levels are. In line with this, the objective of this research was to investigate the digital citizenship levels of the participants and how much they are knowledgeable about being conscious digital citizens. Totally, 196 students from an ELT department of a state university in Turkey participated in the study. The study was carried out with a quantitative research method in the 2021-2022 spring semester, and data were collected through the 5-point Likert type “Digital Citizenship Scale”. Responses were evaluated by SPSS v26 statistical package program and based on the findings, it was indicated that almost all dimensions of digital citizenship were met by the participants. Since there was almost no statistically significant in terms of gender, age, and grade variables, the highest dimensions were found at digital commerce and digital responsibility levels.  This current study will pay the way for educators, instructors, curriculum designers, and materials developers to review, redesign and reevaluate the existing language teaching programs. Students will also be aware of their weaknesses and strengths about digital citizenship and realize the significance of the concept of digital citizenship.